Analysis of the dichloromethane and methanol extracts of eugenia palembanica - Nabihah, Hamdan (Universiti Malaysia Sarawak, (UNIMAS), 2008)
Eugenia palembanica is one of the Myrtaceae families and can be found in Malaysia. Study on the extracts of crude cyclohexane, EtOAc, DCM and MeOH was carried out. The extracts were analyzed with analy1ical TLC and crude extract were then further subjected to fractionate with CC and other chromatography and spectroscopy procedure. Certain fractions from CC was selected for further isolation and purification work using PTLC before subjected to spectroscopic analysis which arc includes NMR and FTIR